Understanding the Pathophysiology of Exosomes in Schistosomiasis: A New Direction for Disease Control and Prevention - Yuan, Yue; Zhao, Jianping; Chen, Min; Liang, Huifang; Long, Xin; Zhang, Bixiang; Chen, Xiaoping; Chen, Qian (Frontiers in Immunology, 2021)
Schistosomiasis is a parasitic disease endemic to freshwater areas of southeast Asia, Africa, and South America that is capable of causing serious damage to the internal organs. Recent studies have linked exosomes to the progression of schistosomiasis. These structures are important mediators for intercellular communication, assist cells to exchange proteins, lipids, and genetic material and have been shown to play critical roles during host-parasite interactions. This review aims to discuss the pathophysiology of exosomes in schistosomiasis and their roles in regulating the host immune response. Understanding how exosomes are involved in the pathogenesis of schistosomiasis may provide new perspectives in diagnosing and treating this neglected disease.